Effect of Dopant on Transport Properties of Polypyrrole Conducting/Electroactive Films - Ansari Khalkhali, Reza (Asian Journal of Chemistry, 2016)
This paper deals with the effect of the dopant counterion on transport of potassium cation across polypyrrole conducting / electroactive polymers used as stand alone films. Polypyrrole as free standing films or membranes doped with two different types of dopants, p-toluene sulfonate and p-dodecyl benzene sulfonate were synthesized electrochemically from aqueous solutions under optimized conditions. Controlled potential transport of K+ ions from KCl solution was studied across the polypyrrole membranes at room themperature using an especially designed electrochemical cell. It was found that polypyrrole doped p-toluene surfonate conducting electroactive membranes show ion transport through membrane only with applying potential. Polypyrrole membranes doped with large size dopants such as polypyrrole doped p-dodecyl benzene sulfonate do not show any measurable ion transport across the membrane with or without applying potential